Stanford neuromodulation therapy for treatment-resistant depression: a systematic review - Lan, Xian-Jun; Cai, Dong-Bin; Liu, Qi-Man; Qin, Zhen-Juan; Pridmore, Saxby; Zheng, Wei; Xiang, Yu-Tao (Frontiers in Psychiatry, 2023)
Objective This systematic review of randomized controlled studies (RCTs) and observational studies evaluated the efficacy and safety of stanford neuromodulation therapy (SNT) for patients with treatment-resistant depression (TRD). Methods A systematic search (up to 25 September, 2023) of RCTs and single-arm prospective studies was conducted. Results One RCT (n = 29) and three single-arm prospective studies (n = 34) met the study entry criteria. In the RCT, compared to sham, active SNT was significantly associated with higher rates of antidepressant response (71.4% versus 13.3%) and remission (57.1% versus 0%). Two out of the three single-arm prospective studies reported the percentage of antidepressant response after completing SNT, ranging from 83.3% (5/6) to 90.5% (19/21). In the three single-arm prospective studies, the antidepressant remission rates ranged from 66.7% (4/6) to 90.5% (19/21). No severe adverse events occurred in all the four studies. Conclusion This systematic review found SNT significantly improved depressive symptoms in patients with TRD within 5 days, without severe adverse events.